Off-the-shelf proximity biotinylation for interaction proteomics - Irene Santos-Barriopedro (Nature Portfolio, 2021)
Proximity biotinylation is a powerful tool to profile interactomes, but it requires genetic engineering of the target protein. Here, the authors develop a proximity biotinylation enzyme that can be directed to the target using antibodies, enabling interactome profiling of endogenous proteins or PTMs.